SCIENCE LITERACY IN PHYSICS LESSONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article is devoted to the problem of developing students' scientific literacy in teaching physics at school. A set of competencies is proposed, where special attention is paid to developing students' functional literacy and interest in the natural sciences, and through it - physics.